Tris(pyrazolyl)phosphines with copper(i): from monomers to polymers. Issue 5 (24th November 2015) - Tazelaar, Cornelis G. J.; Nicolas, Emmanuel; van Dijk, Tom; Broere, Daniël L. J.; Cardol, Mitchel; Lutz, Martin; Gudat, Dietrich; Slootweg, J. Chris; Lammertsma, Koop
Abstract : Ditopic tris(pyrazolyl)phosphines are synthesized and coordinated to Cu(i ), leading to monomers and to a polymeric complex, depending on the ligand substituents. Abstract : The parent tris(pyrazolyl)phosphine and its 3, 5-Me2, 3-Ph, and 3- t -Bu derivatives have been prepared by a simple procedure and show modest Lewis basicity of the phosphorus apex as was established by the magnitude of the 1 J P, Se coupling constant of the phosphine selenides. Because of the chelating properties of both the N- and P-sites, neutral phosphorus-centered scorpion ligands allow coordination modes that are unavailable to the abundantly used anionic tris(pyrazolyl)borate scorpionates as we established for Cu(i )-complexation. The substituted P-scorpion ligands only allow for N-coordination, as the P-apex is presumably less accessible. Two X-ray crystal structures were obtained for the Cu-complex of tris(3, 5-dimethylpyrazolyl)-phosphine with acetonitrile and triphenylphosphine in the fourth coordination site. The parent P-scorpion ligand can chelate with both its pyrazolyl groups and its P-apex with the product depending on the ratio in which it is mixed with the Cu(i ) complex. Reacting two equivalents of the ligand with [Cu(MeCN)4 ][PF6 ] resulted in a complex in which Cu is coordinated to the three pyrazolyl groups of one ligand and to the P-apex of the other ligand as confirmed by an X-ray crystal structure determination and a DFT computational analysis. Reacting the ligand and the Cu(i ) complex in an equimolar ratio resulted in a remarkable one-dimensional P-scorpion coordination polymer for which a single crystal X-ray structure could be determined. A detailed analysis of the structural features is presented.